Optimal cost wide area measurement system incorporating communication infrastructure - Singh S.P.; Singh S.P. (My University, 2025)
A wide area measurement system installation cost minimisation and observability maximisation using binary gravitational search algorithm have been reported. Various methods have been employed in the past to determine the optimal locations of devices to retain the observability of the system. However, the costs of communication infrastructure (CI) from phasor data concentrator to phasor measurement units (PMUs) have not been given proper attention. To address this issue, the PMU placement problem has been formulated incorporating the cost of CI also in this study. Contingency cases have also been included to improve the reliability of the system. Besides, the effects of the presence of preinstalled PMUs have been considered. The results obtained for IEEE 14-bus, 30-bus and 118-bus systems have been compared with other methods in the literature. The test results reveal that the proposed methodology produced the PMU locations with higher observability and lesser distance path of establishing communication link compared to an existing method. © 2017, The Institution of Engineering and Technology.